Identifying research priorities in anaesthesia and perioperative care: final report of the joint National Institute of Academic Anaesthesia/James Lind Alliance Research Priority Setting Partnership. Issue 12 (16th December 2015) - Boney, Oliver; Bell, Madeline; Bell, Natalie; Conquest, Ann; Cumbers, Marion; Drake, Sharon; Galsworthy, Mike; Gath, Jacqui; Grocott, Michael P W; Harris, Emma; Howell, Simon; Ingold, Anthony; et al.
Abstract : Objective: To identify research priorities for Anaesthesia and Perioperative Medicine. Design: Prospective surveys and consensus meetings guided by an independent adviser. Setting: UK. Participants: 45 stakeholder organisations (25 professional, 20 patient/carer) affiliated as James Lind Alliance partners. Outcomes: First 'ideas-gathering' survey: Free text research ideas and suggestions. Second 'prioritisation' survey: Shortlist of 'summary' research questions (derived from the first survey) ranked by respondents in order of priority. Final 'top ten': Agreed by consensus at a final prioritisation workshop. Results: First survey: 1420 suggestions received from 623 respondents (49% patients/public) were refined into a shortlist of 92 'summary' questions. Second survey: 1718 respondents each nominated up to 10 questions as research priorities. Top ten: The 25 highest-ranked questions advanced to the final workshop, where 23 stakeholders (13 professional, 10 patient/carer) agreed the 10 most important questions: ▸ What can we do to stop patients developing chronic pain after surgery? ▸ How can patient care around the time of emergency surgery be improved? ▸ What long-term harm may result from anaesthesia, particularly following repeated anaesthetics? ▸ What outcomes should we use to measure the 'success' of anaesthesia and perioperative care? ▸ How can we improve recovery from surgery for elderly patients? ▸ For which patients does regional anaesthesia give better outcomes than general anaesthesia? ▸ What are the effects of anaesthesia on the developing brain? ▸ Do enhanced recovery programmes improve short and long-term outcomes? ▸ How can preoperative exercise or fitness training, including physiotherapy, improve outcomes after surgery? ▸ How can we improve communication between the teams looking after patients throughout their surgical journey? Conclusions: Almost 2000 stakeholders contributed their views regarding anaesthetic and perioperative research priorities. This is the largest example of patient and public involvement in shaping anaesthetic and perioperative research to date.